UPAYA PEMERINTAHAN KOTA PEKANBARU MENYELESAIKAN KONFLIK LAHAN MASYARAKAT DI KECAMATAN TENAYAN RAYA TAHUN 2021 - Kurniawan, Wahyu; ', Adlin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
In Pekanbaru there is a land conflict involving the community and the government, the community disagrees with the ownership of their land in the public interest. The community opposes this land conflict by reporting it to Commission I of the Pekanbaru City DPRD. The theory used in this study is that the role of the government is in accordance with its functions, including: 1. As a facilitator, local governments can accelerate development through improving the attitudinal environment, which is related to improving licensing and service procedures, as well as establishing areas to strengthen the arrangement of spatial dimensions in development . 2. Negotiations can measure the government's role in negotiating or negotiating can be seen from the efforts made such as identifying problems, seeking and gathering information from each in conflict. 3. Mediation of conflict control by means of mediation is carried out if both parties in conflict agree to appoint a third party as a mediator. Data collection techniques used in this study were interviews and documentation. This research was conducted in Tenayan Raya District, Pekanbaru City. The results of the study show that the process of implementing land consolidation for the Tenayan Raya Ring Road has been carried out optimally, because the government plays a role through participation, negotiation and mediation. The obstacles faced by the Pekanbaru city government in solving consolidation problems are partly due to the lack of public knowledge about the purpose and benefits of land consolidation. Then most of the land affected by consolidation is family land with collective ownership. Keywords: Government Efforts, City of Pekanbaru, Land Conflicts